Responsabilidad social empresarial y su relacion con los servicios de las lubricadoras del cantón Quevedo, año 2015. - Moran Muñoz, Karla Ibeth (2015)
This research project was based on an analysis of corporate social responsibility and the lubricadoras services in the Quevedo canton, which currently has 43 lubricadoras distributed in the different parishes of the canton. To extract the necessary information on research made use of customer surveys and lubricadoras owners, giving them the information needed to obtain relevant findings in this investigation. Manifests serving as the first objective of the research found that currently 94% of managers surveyed Canton lubricadoras Quevedo said that no corporate social responsibility activities are carried out because they have no knowledge about this topic, and that 97 % of managers would be willing to run the CSR as this will allow its customers, suppliers and the community see microenterprise contributes to the development of society. Through the Ethos indicators of corporate social responsibility in the Canton lubricadoras components Quevedo by community support, corporate image, quality of work life and community improvement are not finished developing their CSR properly assessed and that does not have some of the subcomponents. 59% of customers surveyed in the canton lubricadoras Quevedo said that if you feel satisfied with the support provided by its current lubricator service because they offered them promotions and price competition in relation to their products are cheaper Keyword • Corporate social responsibility • Ethos Indicators • Sustainable development • Community • Employment stability